Childhood, adolescent and early adult body mass index in relation to adult mortality: results from the British 1946 birth cohort. Issue 3 (1st October 2010) - Strand, Bjørn Heine; Kuh, Diana; Shah, Imran; Guralnik, Jack; Hardy, Rebecca
Abstract : Background: Adult body mass index (BMI) has been consistently related to mortality, but little is known about the impact of earlier life BMI on adult mortality. The aim is to investigate the impact of childhood, adolescent and early adult BMI on premature adult all-cause mortality. Methods: The British 1946 cohort study was used to assess the association of BMI in childhood, adolescence and adulthood with mortality 26–60 years (332 deaths). 4462 (83%) respondents were available for analysis at age 26 years. Splines were used in Cox regression to model the associations between BMI and mortality. Results: In both genders, adult BMI from 20 years onwards showed a consistent U-shaped relationship with adult mortality (overall p value <0.05 for BMI at ages 20, 26 and 36 years). In women, a similar relationship was observed for adolescent BMI at 15 years (p=0.02); the HR comparing women with low BMI (2 SDs below mean) versus mean BMI was 2.96 (95% CI 1.26 to 6.97). The corresponding HR for women with BMI 2 SDs above the mean was 1.97 (0.95 to 4.10). BMI in childhood was generally not associated with adult mortality except female BMI at 4 years where a U-shaped relationship was observed (p=0.02); HR for BMI 2 SDs below mean versus mean was 2.13 (0.97 to 4.70) and the corresponding HR for 2 SDs above the mean was 1.67 (0.85 to 3.28). This association was not attenuated by subsequent BMI change or mediators. Conclusions: High and low BMI from early adulthood were related to adult premature mortality suggesting that promoting a normal weight in early adulthood could prevent premature mortality.